Proceedings of the 2015 International Conference on Sustainable Energy and Environmental Engineering 2015
DOI: 10.2991/seee-15.2015.14
|View full text |Cite
|
Sign up to set email alerts
|

Transesterification of Waste Cooking Oil to Biodiesel over Calcined Hydroxy Sodalite (HS) Catalyst: A preliminary investigation

Abstract: Abstract-In this article, preliminary investigation on the use of hydroxy sodalite (HS) as a solid catalyst for the transesterification of waste cooking oil (WCO) to biodiesel is presented. Hydroxy sodalite was synthesized in our laboratory via the conventional hydrothermal synthesis technique and the crystals were used as basic solid catalyst to convert waste cooking oil to biodiesel. Physicochemical properties of the as-synthesized HS catalyst were obtained using Fourier Transform Infrared Spectroscopy (FT-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…By increasing the synthesis time to 24 h, the morphology of the resultant S-24 sample, as presented in Figure 2c, evolved into agglomerated thread, ball-like crystals. The hierarchical ball-like morphology is commonly associated with HS zeolite [9]. In spite of the above, the sample in question exhibited a very low HS crystalline phase (18%).…”
Section: Effect Of Hydrothermal Synthesis Time On Catalyst Morphologymentioning
confidence: 99%
“…By increasing the synthesis time to 24 h, the morphology of the resultant S-24 sample, as presented in Figure 2c, evolved into agglomerated thread, ball-like crystals. The hierarchical ball-like morphology is commonly associated with HS zeolite [9]. In spite of the above, the sample in question exhibited a very low HS crystalline phase (18%).…”
Section: Effect Of Hydrothermal Synthesis Time On Catalyst Morphologymentioning
confidence: 99%
“…Its possession of higher flashpoint in comparison to petroleum-derived diesel makes it one of the safest and non-toxic fuels option (Aransiola et al, 2013). Chabisha P Makgaba and Daramola (2015) observed that the application of biodiesel within a diesel internal combustion system improved the lubricity of the system and extended the catalytic converters life when compared to the base system. The system production process and general utilisation cuts down emissions drastically to about seventy-eight percent when compared to petroleum-derived diesel.…”
Section: Introductionmentioning
confidence: 99%
“…Binder (% wt) Workability e agglomerated ball-like morphology is commonly associated with hydroxysodalite zeolite [40]. It is evident that the morphological representation of hydroxysodalite and mixture with others zeolite types through SEM data does not always allow the particular phase identity [41].…”
Section: Samplementioning
confidence: 99%